Konsep Zikir Darajah Dalam Disiplin Ilmu Tarekat - Abdul Manam, M.; Thahirah, Hassan Basri; Faudzinaim, Badaruddin (2014)
Al-dhikr (remeberance of God) is regarded as an effective disciple of sufi order (tariqa institution) in approaching God and seeking His Pleasure. Although the practice of al-dhikr is common among ordinary Muslims, the sufis differentiate the concept of al-dhikr into two categories namely as dhikr darajah and dhikr hasanah. Facts which were gathered from scholars’ pieces and other relevant sources were analysed through inductive and deductive method. The finding result shows that, there are differences between dhikr darajah and dhikr hasanah practices. Dhikr darajah has its own practices which involves the mursyid guidance, prior recitation of dhikr, specific rules, specific exercises, syeikhs’ silsila, ay ah, talqin and irsyād. Hence, this article reveals the differs.